Conceptual modeling to support system‐level decision‐making: An industrial case study from the Norwegian energy domain. Issue 2 (30th November 2022) - Engen, Siv; Muller, Gerrit; Falk, Kristin
Abstract: This article explores conceptual modeling to support system‐level decision‐making during concept evaluation. The system‐level decisions made in the concept phases decide most of the systems' value and cost. The context for our research is the Norwegian energy domain. Through an industrial case study in a global subsea system supplier company, we have explored conceptual modeling to support system‐level decision‐making in the conceptual phase. From the insights and learnings gained in the industry case, the article proposes an approach for using conceptual modeling to support System‐Level Decision‐Making. Further, the article presents three examples of applications to demonstrate the use of the approach. To evaluate the approach's usefulness in the industrial setting, we conducted a survey of 37 engineers in the company of research. The engineers perceive that using the approach would improve awareness of the system context and support a holistic mindset. Furthermore, the engineers perceive the conceptual models as efficient for knowledge sharing and communication, especially in meetings between technical and non‐technical personnel. The engineers identify simplicity as a top benefit of the approach but also as a concern. Balancing the need for abstracting with the need for being specific is a crucial challenge in modeling. The survey also shows concerns about the implementation of the approach and the effort required to use the approach in daily work. The primary outcome of the research is insights into how conceptual modeling can support system‐level decision‐making in the industrial context.